The endeavour of Malaysian muslim NGOs in spreading the message of peace in Malaysia: activities and challenges - Ahmad H.Osman, Rahmah (2017)
This paper investigates the efforts of Malaysian Muslim NGOs in spreading peace in our current time, a time of hyper-volatility overshadowed by the threat of extremism. Instead of taking an empirical approach to this investigation, this paper will take a cultural-critical approach, drawing on the theories of Western and Muslim intellectuals in order to gain greater insight into the peace-promoting efforts. The paper opens by providing a justification for this cultural-critical approach; the opening also explains why three major Malaysian NGOs have been used as a representative example for this investigation. The second part of the paper discusses the importance of creating counter-narratives on Islam that help defrocking extremists of their pseudo-religious authority. The endeavours of the NGOs in Dawah will be examined. Part three outlines the unique narrative on Islam that has been historically dominant in Malaysia and how this helps in forming a counter-narrative. Part four analyses the roots of terrorist violence and sees how the NGOs try to tackle these roots via social projects. The fourth part looks into the sense of alienation that causes people to opt for terror instead of peace. The NGOs role in counselling is highlighted. Part five looks into why the NGOs stress ethics as a means of promoting peace. The sixth part points to how the NGOs diffuse rising frustration among Muslims at the increased injustice that the Ummah is facing. The paper concludes that the success of Malaysian Muslim NGOs in spreading peace has been due to correctly understanding the threat of extremism, and also due to finding effective alternatives to extremism; thus, allowing the NGOs to create a culture of peace in Malaysian society.